Development of a Smartphone-Based Prototype of a Water Multistage Fitness Test Application Instrument - Ardhika Falaahudin; Dody Tri Iwandana; Fajar Vidya Hartono; Ali Md Nadzalan; Nizar Raihan Potutu; Afroga Muhhakat Destri Putra; Agus Supriyanto (CV. Creative Tugu Pena, 2026)
This study aims to: (1) Develop a water MFT test instrument to measure the aerobic endurance of KU-1 swimmers. (2) Design an AFA smartphone application as a database for the aerobic endurance of KU-1 swimmers. (3) Analyze the feasibility of a smartphone-based AFA water MFT instrument application for measuring the aerobic endurance of KU-1 swimmers. This research is a Research and Development (R&D) study with an ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design. The results of the study showed that: (1) The results of the endurance test on land obtained a range of values ​​​​of levels 8.2-8.8 in the very poor category, a range of values ​​​​of levels 8.8-9.4 in the poor category, a range of values ​​​​of 9.4-10.0 in the sufficient category, a range of values ​​​​of levels 10.0-10.6 in the good category, and a range of levels 10.6-11.2 in the very good category. The results of the endurance test in water obtained a range of values ​​​​of levels 3.5-4.0 in the very poor category, a range of values ​​​​of levels 4.0-4.6 in the poor category, a range of values ​​​​of 4.6-5.1 in the sufficient category, a range of values ​​​​of levels 5.1-5.7 in the good category, and a range of levels 5.7-6.2 in the very good category. (2) The results of the assessment of material experts for physical conditions 1 and 2 were declared suitable for use with a good percentage of 41.7% and a very good percentage of 58.3%. The results of the assessment of swimming practitioner 1 with a good percentage of 12.5% ​​and very good 87.5%. While swimming practitioner 2 with a good percentage of 20.8% and very good 79.2%. So the application is declared suitable for use. The results of the media expert assessment are declared suitable for use with a good percentage of 18.8% and very good of 81.2%. (3) The results of small-scale tests obtained the results that athletes who have aerobic endurance are categorized as very good 3 athletes with a percentage of 20%, good 3 athletes with a percentage of 20%, sufficient 2 athletes with a percentage of 13.3%, less 2 athletes with a percentage of 13.3%, and very less 5 athletes with a percentage of 33.3%. The results of the large-scale test showed that 7 athletes with good aerobic endurance (23.3%), 9 athletes with adequate aerobic endurance (30%), 7 athletes with poor